2021
DOI: 10.1021/acs.molpharmaceut.1c00459
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Modified Nanoparticles Self-Assembled from Linoleic Acid-Conjugated Chitosan for the Codelivery of miR34a and Doxorubicin in Resistant Breast Cancer

Abstract: In this study, a chitosan-based, self-assembled nanosystem that codelivered microRNA34a (miR34a) and doxorubicin (Dox) with hyaluronic acid (HA) modification (named CCmDH NPs) was developed to reverse the resistance of breast cancer (BCa) cells to Dox. The CCmDH NPs had a diameter of 180 ± 8.3 nm and a ζ potential of 16.5 mV with a slow-release effect for 96 h. The codelivery system could protect miR34a from nuclease and serum degradation and transport miR34a and Dox into drug-resistant MCF-7/A cells. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Serum Stability of the H−C@C/siRNA NPs. According to the method proposed by Yang et al, 31 FBS was mixed with naked siRNA and nanoparticles in equal volumes and incubated at room temperature for 1, 3, 6, 12, and 24 h, respectively. The degradation of siRNA was analyzed by electrophoresis on a 3% agarose gel at 80 V for 30 min.…”
Section: Analysis Of Co-assembly Interactionmentioning
confidence: 99%
“…Serum Stability of the H−C@C/siRNA NPs. According to the method proposed by Yang et al, 31 FBS was mixed with naked siRNA and nanoparticles in equal volumes and incubated at room temperature for 1, 3, 6, 12, and 24 h, respectively. The degradation of siRNA was analyzed by electrophoresis on a 3% agarose gel at 80 V for 30 min.…”
Section: Analysis Of Co-assembly Interactionmentioning
confidence: 99%
“…C-A-Au NPs incorporating GFT-miR125b preferably accumulated at the tumor area in the Lewis lung carcinoma (LLC) xenograft tumor model and inhibited EGFR signaling, leading to tumor growth inhibition. A novel nanocarrier, hyaluronic acid (HA)-modified and conjugated linoleic acid (CLA)-grafted chitosan nanoparticles co-loaded with miR-34a and DOX, has been formulated [ 125 ]. Therapeutic administration of these nanosystems resulted in 73.7% tumor inhibition of MCF-7/A tumor xenografts in mice, which was higher than the other treatment arms lacking the targeting ligand, the miR-34a, or DOX.…”
Section: Nanocarrier Systems To Deliver Mirna-based Therapeuticsmentioning
confidence: 99%
“…The experimental data showed that CCmDHNPs suppressed and facilitated apoptosis by modulating protein expression of B-cell lymphoma-2 (Bcl-2) and poly (ADP-ribose) polymerase (PARP), producing sound inhibitory effects on xenograft tumors in nude mice, as well as effectively suppressed invasion, metastasis, and adhesion of breast cancer cells by regulating the levels of E-cadherin, N-cadherin, MMP2, CD44, and Snail molecules. CCmDHNPs have shown good inhibitory effects on the growth and migration of anti-DOX metastatic BCa tumors, providing an effective and novel therapeutic strategy for breast cancer treatment ( Yang et al, 2021 ).…”
Section: Ha Hybrid Nddssmentioning
confidence: 99%